2021
DOI: 10.1055/s-0041-1729882
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparative Functional and Aesthetic Outcome Study of Muscle versus Cutaneous Free Flaps for Distal Upper Extremity Reconstruction

Abstract: Background Function and cosmesis are crucial in upper extremity reconstruction. Yet, there persists a lack of outcome evaluations, particularly regarding differences between free flap types. Methods In a single-center retrospective analysis, outcomes were compared between patients with cutaneous or muscle free flaps for distal upper extremity reconstruction between 2008 and 2018. The Disabilities of Arm, Shoulder and Hand -Score, Michigan-Hand (MHQ), and Short Form 36 Health Survey (SF-36) Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…To this end, perforator flaps offer certain advantages that have contributed to their growing success over the past decades (Morris et al, 2010). Particularly in extremity reconstruction, the anterolateral thigh perforator (ALT) free flap has gained widespread popularity in this context, due to its easily accessible donor site, relatively long pedicle, reliable perforasome, and pliability (Thomas et al, 2021;Wei et al, 2002).…”
mentioning
confidence: 99%
“…To this end, perforator flaps offer certain advantages that have contributed to their growing success over the past decades (Morris et al, 2010). Particularly in extremity reconstruction, the anterolateral thigh perforator (ALT) free flap has gained widespread popularity in this context, due to its easily accessible donor site, relatively long pedicle, reliable perforasome, and pliability (Thomas et al, 2021;Wei et al, 2002).…”
mentioning
confidence: 99%
“…For the proximal side of the thigh, pedicled RAM was the most commonly used, consistent with the reports in the literature 31 . Contrarily, distal limb reconstructions were usually performed with free flaps 32,33 . In the free flap, the donor site of the flap was decided according to the operator's preference.…”
Section: Discussionmentioning
confidence: 61%
“…31 Contrarily, distal limb reconstructions were usually performed with free flaps. 32,33 In the free flap, the donor site of the flap was decided according to the operator's preference. We preferred free ALT because this flap has the advantage of a long vascular pedicle with large-caliber vessels and is suitable as a flow-through flap and thin flap.…”
Section: Discussionmentioning
confidence: 99%
“…While established muscle and fasciocutaneous flaps have been used for extremity reconstructions and have demonstrated comparable results in limb salvage [32,33], recent studies have shown that fasciocutaneous flaps have fewer wound healing disorders and partial flap losses [34,35]. During the decision-making process, the reconstructive microsurgeon must consider various factors when selecting a flap, such as its ability to withstand mechanical stress and remain thin and pliable to ensure mobility.…”
Section: Discussionmentioning
confidence: 99%